Release of replication termination controls mitochondrial DNA copy number after depletion with 2′,3′-dideoxycytidine - Brown, Timothy A. (Oxford University Press, 2002)
Although cellular mitochondrial DNA (mtDNA) copy number varies widely among cell lines and tissues, little is known about the mechanism of mtDNA copy number control. Most nascent replication strands from the leading, heavy-strand origin (O(H)) are prematurely terminated, defining the 3′ boundary of the displacement loop (D-loop). We have depleted mouse LA9 cell mtDNA to ∼20% of normal levels by treating with 2′,3′-dideoxycytidine (ddC) and subsequently allowed recovery to normal levels of mtDNA. A quantitative ligation-mediated PCR assay was used to determine the levels of both terminated and extended nascent O(H) strands during mtDNA depletion and repopulation. Depleting mtDNA leads to a release of replication termination until mtDNA copy number approaches a normal level. Detectable total nascent strands per mtDNA genome remain below normal. Therefore, it is likely that the level of replication termination plays a significant role in copy number regulation in this system. However, termination of D-loop strand synthesis is persistent, indicating formation of the D-loop structure has a purpose that is required under conditions of rapid recovery of depleted mtDNA.